SHILPA GUPTA: AN ARTIST CONCEPTUALIZING WITH TECHNOLOGY - Babbar, Akshi; Singh, Gurcharan (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India follows the catchy, trendy, uncertain, and spontaneous concepts of new media art for the last few decades. New media practice in India has dealt with issues of identity, critiques of violence, narrative, and performance, and other subjects that come under the umbrella of new issues. New media art began to appear in India since the inception of the 21st century, but it showed in the works of artists like Vivan Sundaram, Nalini Malam, Ved Nayar, Rummana Hussain in the 1990s. New media ideologically mixed art with scientific craft, which resulted in an amplified narrative of our country and world that is a union of different creative languages. New media create a futuristic ethos in the art that is developing every second. It is a medium that symbolizes freedom of mediums, as it is spontaneous and enough. In all this, Shilpa Gupta came as a ‘blind star and star blind’. Shilpa Gupta is one of the leading contemporary, influential, and critically acclaimed new media artists of India’s new generation of international artists. A transcultural artist even when influenced with regional specificity. She considers new media art (a web of technology) as a key part of today’s existence, and, ensuing, prefers various forms of cutting-edge technology as the vehicle for her interactions with the viewer. Although Gupta’s works are developed largely through technological means their significance lies in their candid communication, the various issues that shape contemporary life, particularly the lives of young and adults. Her work is often coded with meanings that are not always instantly available but require the efforts of the viewer. Uniquely and humorously, Gupta reminds us of the danger of taking for granted – that it is indeed technology that connects us to the world. She is an artist who deals with her viewers, her audience is 70 percent part of her artwork. She brings reality from a new perspective.